Hoe een Franse ingenieur over de Abdij van Middelburg in 1812 oordeelde - G.Sophia van Holthe tot Echten (Bulletin KNOB, 1990)
In 1810 the province of Zealand became a part of the great French empire and was officially named 'Département des Souches de l'Escaut' (Departement of the Mouthes of the Scheldt) with Middelburg as its capital. A prefecture had to be set up here and the old seat of the former centre of government, the Abbey in Middelburg, was considered the best site for it. Napoleon attached great value to architectural provisions (mainly for military purposes) because of the strategic importance of this department. However, there was no local architect to meet the new requirements and who could cooperate with the French experts at their level.